Implementasi dan Tantangan Hukum Non Fungitable Token Terhadap Regulasi di Indonesia: Prespektif Hukum Perdata - Ibnu Usman, Syahrehan (Zaaken: Journal of Civil and Business Law, 2025)
The digital economy has grown rapidly with the emergence of blockchain technology, which serves as the foundation for digital assets such as Non-Fungible Tokens (NFTs). NFTs enable unique digital ownership of artworks, music, and other digital assets. However, regulations governing NFTs in Indonesia remain limited, posing legal challenges, particularly in multi-party transactions and ownership protection. This study aims to analyze the regulations governing NFT ownership in Indonesia, identify legal challenges arising in multi-party transactions, and evaluate dispute resolution mechanisms in NFT transactions. Using a normative approach and descriptive analysis method, this research finds that existing regulations do not specifically accommodate the unique characteristics of NFTs, leading to legal uncertainty in ownership and copyright protection. Therefore, more comprehensive and specific regulations are needed to create legal certainty and support the development of the NFT industry in Indonesia.